Monetary policy implementation and payment system modernization - Jonathan Witmer (Bank of Canada, 2020)
24/7 payment settlement may impact the demand for central bank reserves and thus could have an effect on monetary policy implementation. Using the standard workhorse model of monetary policy implementation (Poole, 1968), we show that 24/7 payment settlement induces a precautionary demand for central bank balances. Absent any changes or response by the central bank, this will put upward pressure on the overnight interest rate in a standard corridor system of monetary policy implementation. A floor system is much less sensitive to this change, as long as excess balances are large enough.
Keywords: E; E4; E40; E42; E43; 330; Monetary policy implementation; Payment clearing and settlement systems